Analisis Faktor-Faktor Pengambilan Keputusan Mahasiswa Memilih Program Studi Administrasi Bisnis pada Fakultas Ilmu Sosial dan Ilmu Politik UPN “Veteran” Jawa Timur - Rusdi Hidayat; Acep Samsudin; Firdausii Khoirunnisa; Alissa Azizah Herman Susilo; Rangga Eka Saputra; Daivan Putra Tanzaga; Ely Nanda Khamdiyah (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Education is an essential part of a human being's life, therefore decision-making in matters of education is something that really needs attention. One of them is making the decision to take the study program to be pursued in Higher Education, the many choices that can be made make prospective students need to make the right decision in deciding which study program to pursue. The research method used was a qualitative method with a questionnaire as a data collection technique, while the research participants came from business administration study program students from the East Java